Immunomorphologic profile and Epstein–Barr virus status of a cohort of 35 cases of extranodal natural killer/T-cell lymphoma, nasal type of upper aerodigestive tract from a tertiary care center in South India. Issue 6 (1st June 2013) - Bugalia, Amit; Manipadam, Marie Therese; Nair, Sheila
Abstract: Extranodal natural killer (NK)/T-cell lymphoma, nasal type (EN-NK/T-NT) is a lymphoma of NK-cell or cytotoxic T-cell origin, which occurs most commonly in the upper aerodigestive tract. We have studied the immunomorphologic profile and Epstein–Barr virus (EBV) status of a cohort of 35 cases of EN-NK/T-NT of the upper aerodigestive tract (UADT) diagnosed in our institution during the period May 2002 to April 2012. At our institution these lymphomas constitute 0.7% of total non-Hodgkin lymphomas (NHLs) and 5.1% of total peripheral T-cell lymphomas (PTCLs). The median age at diagnosis was 40 years with a male-to-female ratio of 4:1, and the most common site of involvement was the nasal cavity. Morphologically, the neoplastic cells were predominantly medium sized in most cases. Necrosis and angiocentricity were common histologic features. Thirty cases (85.7%) showed NK-cell immunophenotype, CD3+ (29/30, 96.7%), CD56+ (30/30, 100%) and TIA1/Granzyme B+ (30/30, 100%). Five cases (14.3%) showed cytotoxic T-cell immunophenotype, CD3+ (5/5, 100%), CD56− (5/5, 100%) and TIA1/Granzyme B+ (5/5, 100%). EBV-encoded RNA- in situ hybridization (EBER-ISH) was positive in all 35 cases, whereas EBV latent membrane protein-1 (EBVLMP1) was positive in only 19/35 (54.3%) of cases. In conclusion, this is the first large study from India to report the immunomorphologic profile and EBV association of EN-NK/T-NT, which is known to have geographic variation. The frequency of these lymphomas in our study is comparable to that of Western and European countries and much less than that of Far Eastern countries.